Upaya Guru Dalam Meningkatkan Keterampilan Menulis Melalui Pembiasaan Siswa Di SDN Sidokepung 1 Buduran - Adha, Rafly; kurniawati, rikke (IJPSE Indonesian Journal of Primary Science Education, 2025)
The purpose of this study is to analyze the difficulties of elementary school students in writing skills to gain new knowledge and inventions and to develop existing knowledge. Studies are conducted with elementary school students. The study also aims to analyze the teacher’s efforts in implementing active reading and writing classes. This study is a qualitative study using literary study methods. The techniques for collecting data in this study are done by observation of existing data. Research indicates that early education included more than just teacher responsibility. The parent must also accompany the child to avoid falling behind. While a workable teacher’s effort is to be clean, and classroom grooming, changing the table order to avoid boredom. In addition, teachers should also be able to encourage students by playing before learning and also by singing together. As for the teacher’s obstacle to teaching elementary school students is the often inconducive class atmosphere, the student walking around the class and also the colorless student LKS cause the decline in reading.